Ultrasensitive Molecule Detection Based on Infrared Metamaterial Absorber with Vertical Nanogap (Small Methods 8/2021). Issue 8 (12th August 2021) - Hwang, Inyong; Kim, Mingyun; Yu, Jaeyeon; Lee, Jihye; Choi, Jun‐Hyuk; Park, Su A.; Chang, Won Seok; Lee, Jongwon; Jung, Joo‐Yun
Abstract : Inside Front Cover In article number 2100277, Lee, Jung, and co‐workers develop an ultrasensitive molecule detection platform for surface‐enhanced infrared absorption spectroscopy. Based on using a metamaterial absorber with 10 nm‐thick vertical nanogap processed via nanoimprint lithography and isotropic dry‐etching, a record‐high reflection difference detection signal for a 1‐octacanethiol monolayer molecule is achieved.